INTEGRATING CULTURAL APPROACHES IN EDUCATION: ENHANCING ENGAGEMENT AND EQUITY IN MULTICULTURAL CLASSROOMS - Ashura Sindhu Santhana (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
Education plays a pivotal role in shaping an inclusive society, especially in today’s multicultural world. This research examines the importance of cultural approaches in education, emphasizing how cultural responsiveness in teaching can improve inclusivity and student outcomes. As classrooms grow more diverse, integrating cultural awareness into teaching practices is essential. This paper explores the role of cultural context in pedagogy, investigates methods of fostering inclusivity through culturally responsive teaching, and identifies challenges educators face. Results indicate that a culturally adaptive curriculum not only enhances engagement but also supports equitable academic success. This research contributes to a growing body of work advocating for education systems that respect and reflect diverse cultural backgrounds.